2009
DOI: 10.1002/joc.1996
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of land use land cover on temperature trends over the continental United States: assessment using the North American Regional Reanalysis

Abstract: ABSTRACT:We investigate the sensitivity of surface temperature trends to land use land cover change (LULC) over the conterminous United States (CONUS) using the observation minus reanalysis (OMR) approach. We estimated the OMR trends for the 1979-2003 period from the US Historical Climate Network (USHCN), and the NCEP-NCAR North American Regional Reanalysis (NARR). We used a new mean square differences (MSDs)-based assessment for the comparisons between temperature anomalies from observations and interpolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
101
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 182 publications
(118 citation statements)
references
References 63 publications
10
101
0
1
Order By: Relevance
“…Interestingly, the oil palm and rubber plantations were only slightly warmer than the forests whereas the young oil palm plantations had clearly higher LST than the other vegetated surfaces. For other parts of the world, Lim et al (2005Lim et al ( , 2008, Fall et al (2010) and Weng et al (2004) also observed cooler temperatures for forests and the highest surface temperatures for barren and urban areas. In Indonesia, land transformation is often not instantaneous from forest to oil palm or rubber plantation but can be associated with several years of bare or abandoned land in-between (Sheil et al, 2009).…”
Section: Lst Patterns Across Different Land Use and Land Cover (Lulc)mentioning
confidence: 88%
“…Interestingly, the oil palm and rubber plantations were only slightly warmer than the forests whereas the young oil palm plantations had clearly higher LST than the other vegetated surfaces. For other parts of the world, Lim et al (2005Lim et al ( , 2008, Fall et al (2010) and Weng et al (2004) also observed cooler temperatures for forests and the highest surface temperatures for barren and urban areas. In Indonesia, land transformation is often not instantaneous from forest to oil palm or rubber plantation but can be associated with several years of bare or abandoned land in-between (Sheil et al, 2009).…”
Section: Lst Patterns Across Different Land Use and Land Cover (Lulc)mentioning
confidence: 88%
“…On the other hand, increased urbanization coupled with warmer air temperatures might result in more intense land surface warming, which is an additive effect of land cover and climate changes. Hence, the regional effects of land cover change can offset or magnify changes in global average temperature, and can significantly alter the impacts associated with global warming (Feddema et al, 2005;Fall et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The OMR method is based on the fact that the reanalysis data did not assimilate observed surface information. This method does provide some signatures consistent with the distribution of underlying surface properties [22,[29][30][31][32][33][34][35][36]. However, whether or not the OMR fully represents the impact of LUCC is still controversial [37,38].…”
mentioning
confidence: 99%